2013
DOI: 10.1128/jvi.02073-13
|View full text |Cite
|
Sign up to set email alerts
|

HLA-DPPolymorphisms Affect the Outcomes of Chronic Hepatitis B Virus Infections, Possibly through Interacting with Viral Mutations

Abstract: c Genetic polymorphisms of HLA-DP have been associated with hepatitis B virus (HBV) persistence. We aimed to determine the effect of HLA-DP polymorphisms on the generation of HBV mutations and their interactions on the outcomes of HBV infection. rs3077, rs3135021, rs9277535, and rs2281388 were genotyped in 1,342 healthy controls, 327 HBV clearance subjects, and 2,736 HBV-positive subjects, including 1,108 hepatocellular carcinoma (HCC) patients, using quantitative PCR. HBV mutations were determined by sequenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
67
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(75 citation statements)
references
References 53 publications
(79 reference statements)
6
67
2
Order By: Relevance
“…Virus mutations related to advanced liver disease seem to accumulate along the course of CHB Many of the virus mutations identified here affected genomic positions frequently associated with chronic hepatitis, liver cirrhosis and hepatocellular carcinoma (Table 2) (Yin et al, 2011;Zhang et al, 2013). Remarkably, such mutations were present in both the inactive carrier patient and the immunotolerant ones, supporting the idea of a continuous diversification along the course of CHB, accompanied by the emergence of mutants associated with serious liver conditions.…”
Section: T-cell Epitopessupporting
confidence: 62%
See 1 more Smart Citation
“…Virus mutations related to advanced liver disease seem to accumulate along the course of CHB Many of the virus mutations identified here affected genomic positions frequently associated with chronic hepatitis, liver cirrhosis and hepatocellular carcinoma (Table 2) (Yin et al, 2011;Zhang et al, 2013). Remarkably, such mutations were present in both the inactive carrier patient and the immunotolerant ones, supporting the idea of a continuous diversification along the course of CHB, accompanied by the emergence of mutants associated with serious liver conditions.…”
Section: T-cell Epitopessupporting
confidence: 62%
“…Furthermore, all the study patients presented virus mutations, many of which have been shown recently to correlate with serious liver conditions (Table 2) (Yin et al, 2011;Zhang et al, 2013). The discovery of such mutations in immune-tolerant patients is novel and possibly has been hampered to date due to the limited sensitivity of traditional genotyping approaches (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Of these mutations, A1762T/G1764A has been prospectively shown to be an independent risk factor of HCC (15,26). A1762T/ G1764A and A1762T/G1764A-based combo mutants are potentially selected by the immunocompromised microenvironment predisposed by genetic polymorphisms of key immune and proinflammatory molecules, and in turn promote an aggressive phenotype of HCC, as well as the recurrence of HCC after curative surgery (27)(28)(29)(30). The objective of this study was to clarify whether the baseline HBV mutations can predict the outcome of HBVinfected patients and whether HCC risk contributed by the HBV mutations can be selectively reduced by antiviral treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous epidemiological studies, we found that the HLA-II genetic polymorphisms are statistically associated with the generation of the liver diseasesassociated HBV mutations. The HLA-DP polymorphisms rs3077 (CT + TT vs. CC), rs3135021 (GA + AA vs. GG), rs9277535 (GA + AA vs. GG), and rs2281388 (CC vs. CT + TT) significantly decrease HBV persistence in genotype B HBV-infected subjects; HLA-DP genotypes that promote HBV clearance are associated with a lower prevalence of HBV mutations increasing HCC risk (C1653T, T1674C/G, A1846T, G1896A, preS2 mutations, and preS deletion in genotype C) and a higher prevalence of HBV mutations decreasing HCC risk (G1652A, T1673C, T1674C, G1719T, G1730C, and G1799C in genotype B and A1727T in genotype C); furthermore, significant effects of HBV mutations on cirrhosis and HCC are selectively evident in those with the HLA-DP genotypes that promote HBV persistence [61] . Thus, the HLA-DP polymorphisms affect genotype B HBV clearance, regulate immune selection of viral mutations, and influence cirrhosis and HCC risks contributed by the HBV mutations.…”
Section: Interaction Of Genetic Predispositions Of Immune or Inflammamentioning
confidence: 99%